Water consumption in residential multifamily buildings - Szaflik, Władysław (Instal, 2020)
The article presents the results of research on annual consumption of total water (hot and cold) and hot water in 2019 by residents of sixty-five residential buildings located in several housing estates housing in Szczecin. The value of average annual consumption and standard deviation were determined in terms of total water and hot water per one inhabitant of a tested building. Assuming on the basis that the distribution of the consumption values is normal, the total values and hot water values of the average daily water consumption have been determined, that accounted for each inhabitant, while the likelihood of occurrence with lower values 90%, 95% and 99%.
Keywords: water supply installations; water consumption; hot water consumption